Analysis of Water-Soluble Vitamin Change in Tomato (S.lycopersicum) Due to Ozonolysis of Imidacloprid Degradation Treatment by Using Spectrometry and HPLC Method - Donanita, Tysa; Safni, Safni; Suryati , Suryati (Jurnal Akademika Kimia, 2023)
In this study, the effect of imidacloprid degradation on the reduction of water-soluble vitamins in tomatoes was observed, such as ascorbic acid, pyridoxine, niacin, and thiamine. Analysis was carried out using a spectrophotometer and high-performance liquid chromatography. The degradation method with ozone water for 15 minutes showed a better result than the ozonolysis method because the decrease in levels of water-soluble vitamins is smaller. The percentage decrease of each water-soluble vitamin in the ozone water method is ascorbic acid by 17.103 %, pyridoxine by 6.723 %, niacin by 2.781 %, and thiamine by 0.333 %. Ozone water methods also produce a high percentage of degradation which is 90.56 %.